Short stories and selections for use in the secondary schools - Baker, Emilie K. (Emilie Kip), 1873-1951 (Salt Lake City, UT : Project Gutenberg, 2005)
"Short Stories and Selections for Use in the Secondary Schools" by Emilie K. Baker is a compilation of literary works crafted for the education of high school students, likely produced in the late 19th century. This collection seeks to expose students to a variety of genres and writing styles, with selections ranging from fiction to essays, aiming to enhance their appreciation of literature and critical thinking skills. The book includes works from notable authors, suggesting that it not only serves an educational purpose but also strives to elevate literary taste among young readers. The opening of the compilation provides an overview of the contents and the intention behind the selections. It discusses the challenges that educators face in engaging students with classic literature, highlighting how modern readers often gravitate towards less demanding material. Baker outlines her desire to introduce students to worthy literature, hoping to foster a habit of reading and deeper critical engagement with texts. The introduction emphasizes the importance of literary exposure, illustrating that good literature can have a lifelong impact on personal development and intellectual growth. It sets the stage for the short stories and essays that follow, which aim to captivate and educate young minds. (This is an automatically generated summary.)
A leaf in the storm -- Cats -- An adventure -- For those who love music -- Out of doors -- The taboo -- School days at the convent -- In Brittany -- The Adirondacks -- An ascent of Kilauea -- The fetish -- Salmon fishing in Ireland -- Across running water -- The pine-tree shillings -- The white trail -- A dissertation on roast pig -- The last class -- An Arab fisherman -- The archery contest -- Baby Sylvester -- The address at Gettysburg -- The second inaugural address -- An appreciation of Lincoln -- The elephants that struck -- The luck of Roaring Camp -- The story of Muhammad Din -- A child -- Too dear for the whistle -- Lodging for the night -- A bad five minutes in the Alps -- The gold trail -- Twenty years of Arctic struggle -- The speech in Manchester -- A green donkey driver -- A night in the pines -- Life in old New York -- The bazaar in Morocco -- A battle of the ants -- An African pet -- Animal intelligence -- Buck's trial of strength -- On the Solander whaling ground -- An episode of the French Revolution -- The commander of the faithful -- Walt Whitman -- Heroism in housekeeping -- A youthful actor -- War -- Coon-hunting -- Sight in savages -- The village schoolmaster.
Release date is 2005-01-01
Produced by V-M Österman, Charles Franks and the Online Distributed Proofreading Team
Keywords: Short stories; Readers; English prose literature